Evaluación al programa de la maestría en planeamiento y administración educativos de la universidad técnica de Cotopaxi. - Calderón Yépez, Jaime Vinicio (2017)
The actual research keeps a close relation with the actual politics of the National Government, of the constant assessment to determine failures and with it correct and improve them, in this specific case, the academic offer routing thus to get the so desired academic excellence that being a constant and circular process, this must be done in a permanent form and it doesn’t have an aim but rather it contains cycles and steps of continuous advancement. The assessment that is done in the actual job is guided to the learning environments of the mastery program in planning and educative administration, having as a base to do it the documents issued by the CEAACES which is the entity in charge to ensure the quality of the superior education. The main goal has been to get results that let us to account with data which will serve to develop an improvement plan and for this a mixed approach has been used (quantitative- qualitative) that let us to be flexible in relation to the picking and reading of the obtained information. The results that has been thrown from this job keeps a narrow relation with the reality according to the development of the postgraduate program, obtaining a final score of 57, 49 which is located in an unsatisfying category. Finally we have to take account that in the process of the picking of information , it has been evidenced an important concern from The Direction of the Postgraduate to improve the different kinds of the mastery program that they offer and they have inside their plans to potentiate the learning environments.